Short‐term weight loss patterns, baseline predictors, and longer‐term follow‐up within a randomized controlled trial. (15th October 2013) - Yank, Veronica; Xiao, Lan; Wilson, Sandra R.; Stafford, Randall S.; Rosas, Lisa Goldman; Ma, Jun
Abstract : Objective: To examine weight loss patterns and predictors among participants in a primary care‐based translation study of the Diabetes Prevention Program lifestyle intervention. Design and Methods: Cluster analysis identified short‐term (12‐week) weight loss patterns among 72 intervention participants. Analysis of variance assessed cluster differences in weight loss maintenance at 15‐month follow‐up. Discriminant analysis identified baseline characteristics that best differentiated between clusters. Results: Participants had baseline mean (SD) age of 55.0 (10.8) years and BMI of 31.9 (5.2) kg/m 2 . Cluster analysis identified three short‐term weight loss patterns: modest ( n = 15; 21%), moderate‐and‐steady ( n = 43; 60%), and substantial‐and‐early ( n = 14; 19%). Only participants with the latter two patterns achieved clinically significant (≥5%) short‐term weight loss and maintained it at 15 months. On discriminant analysis, the modest cluster was most differentiated from other clusters by high friend encouragement for dietary change, high obesity‐related problems, and low physical well‐being. The moderate‐and‐steady cluster was differentiated by lower physical activity, family encouragement, and depression symptoms. Conclusion: Results provided insight into the heterogeneity of response to an effective lifestyle intervention by identifying short‐term weight loss patterns and their baseline predictors and relationship to 15‐month success. If replicated, results may help tailor strategies for participant subgroups in weight loss programs.